Preliminary in vitro evaluation of chitosanâgraphene oxide scaffolds on osteoblastic adhesion, proliferation, and early differentiation - Wong, S.H.M. (MDPI AG, 2020)
An ideal scaffold should be biocompatible, having appropriate microstructure, excellent mechanical strength yet degrades. Chitosan exhibits most of these exceptional properties, but it is always associated with sub-optimal cytocompatibility. This study aimed to incorporate graphene oxide at wt of 0, 2, 4, and 6 into chitosan matrix via direct blending of chitosan solution and graphene oxide, freezing, and freeze drying. Cell fixation, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide, alkaline phosphatase colorimetric assays were conducted to assess cell adhesion, proliferation, and early differentiation of MG63 on chitosanâgraphene oxide scaffolds respectively. The presence of alkaline phosphatase, an early osteoblast differentiation marker, was further detected in chitosanâgraphene oxide scaffolds using western blot. These results strongly supported that chitosan scaffolds loaded with graphene oxide at 2 wt mediated cell adhesion, proliferation, and early differentiation due to the presence of oxygen-containing functional groups of graphene oxide. Therefore, chitosan scaffolds loaded with graphene oxide at 2 wt showed the potential to be developed into functional bone scaffolds. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.